2019
DOI: 10.1111/add.14753
|View full text |Cite
|
Sign up to set email alerts
|

Effects of repetitive transcranial magnetic stimulation (rTMS) on craving and substance consumption in patients with substance dependence: a systematic review and meta‐analysis

Abstract: Background and Aims Repetitive transcranial magnetic stimulation (rTMS) is increasingly used as an intervention for treating substance dependence. We aimed to assess evidence of the anti‐craving and consumption‐reducing effects of rTMS in patients with alcohol, nicotine and illicit drug dependence. Methods A systematic review and meta‐analysis of 26 randomized controlled trials (RCTs) published from January 2000 to October 2018 that investigated the effects of rTMS on craving and substance consumption in patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
75
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 62 publications
(139 reference statements)
11
75
0
Order By: Relevance
“…A range of prefrontal neural regions have been targeted with rTMS including superior frontal gyrus (Rose et al, 2011) or medial prefrontal cortex (Hanlon et al, 2017), whereas we focus here on DLPFC targeting. Convergent evidence has suggested that facilitating the left DLPFC or inhibiting the right DLPFC may reduce craving and substance consumption in patients with substance dependence (Zhang et al, 2019). High-frequency excitatory rTMS of the left DLPFC has been reported to be effective in cocaine use disorder [e.g., 15 Hz/8 sessions/100% motor threshold (Terraneo et al, 2016), 15 Hz/10 sessions/100% motor threshold (Politi et al, 2008), and 10 Hz/single session/90% motor threshold (Camprodon et al, 2007)] and nicotine use disorder [e.g., high frequency/13 session/120% motor threshold, deep TMS over bilateral lateral prefrontal and insula (Dinur-Klein et al, 2014), 10 Hz/10 sessions/100% motor threshold, and 20 Hz/8 sessions/110% over the DLPFC (Amiaz et al, 2009;Sheffer et al, 2018)].…”
Section: Introductionmentioning
confidence: 99%
“…A range of prefrontal neural regions have been targeted with rTMS including superior frontal gyrus (Rose et al, 2011) or medial prefrontal cortex (Hanlon et al, 2017), whereas we focus here on DLPFC targeting. Convergent evidence has suggested that facilitating the left DLPFC or inhibiting the right DLPFC may reduce craving and substance consumption in patients with substance dependence (Zhang et al, 2019). High-frequency excitatory rTMS of the left DLPFC has been reported to be effective in cocaine use disorder [e.g., 15 Hz/8 sessions/100% motor threshold (Terraneo et al, 2016), 15 Hz/10 sessions/100% motor threshold (Politi et al, 2008), and 10 Hz/single session/90% motor threshold (Camprodon et al, 2007)] and nicotine use disorder [e.g., high frequency/13 session/120% motor threshold, deep TMS over bilateral lateral prefrontal and insula (Dinur-Klein et al, 2014), 10 Hz/10 sessions/100% motor threshold, and 20 Hz/8 sessions/110% over the DLPFC (Amiaz et al, 2009;Sheffer et al, 2018)].…”
Section: Introductionmentioning
confidence: 99%
“…even when faced with consequences, subjects continue to pursue the drug) (Hu et al, 2019), the possibility of using rTMS to stimulate hypoactive prefrontal cortical neurons, which can then modulate interconnected networks, is appealing (Diana et al, 2017;Madeo and Bonci, 2019;Song et al, 2019). An increasing number of studies have shown anticraving effects following rTMS treatment targeting the PFC (see Ma et al, 2019;Madeo and Bonci, 2019;Zhang et al, 2019), presumably through modulation of the efferent glutamatergic and afferent dopaminergic connections (Diana, 2011;Diana et al, 2017; Figure 1). Therefore, rTMS modulation of mesocorticolimbic pathways in people with substance use disorders may provide therapeutic effects.…”
Section: Rtms In Cocaine and Methamphetamine Abuse -Clinical Researchmentioning
confidence: 99%
“…A recent meta-analysis that looked at single versus multiple sessions of neuromodulation across all addiction domains found that multiple sessions were more effective at reducing craving, with larger effect sizes compared to single sessions (Song et al, 2019). Recent systematic reviews have included several studies that demonstrate anticraving effects with chronic stimulation (Madeo and Bonci, 2019;Zhang et al, 2019). Moreover, in studies where there was no change in craving after the first session, there was a significant anticraving effect by the end of the treatment period (5 days of daily HF-rTMS) for active, but not sham, stimulation (Su et al, 2017).…”
Section: Hz or Greatermentioning
confidence: 99%
See 1 more Smart Citation
“…rTMS has been shown to be effective in large randomized controlled trial studies in a range of neuropsychiatric diseases including depression and obsessive-compulsive disorder (10,11). With respect to disorders of addiction, a meta-analysis revealed a significant anti-craving effect of excitatory rTMS of the left dorsolateral prefrontal cortex (DLPFC) in patients with substance dependence (12). In AUD specifically, one study suggested that high-frequency rTMS on either right or left DLPFC significantly reduce craving scores in patients (13).…”
Section: Introductionmentioning
confidence: 99%